ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA POKOK BAHASAN MATRIKS DI KELAS XI MA - Fetty Nuritasari; Sri Indriati Hasanah; Aan Sholehoddin (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2017)
This research is aimed to know about location and type of errors the students do and contributing factor.The research subject are students on the elevent grade in MA. The methods used for data collection in this research are tests and interviews. The conclusion of this research are a) the location of students error on XI grade MA in solving the matrix problem are: misunderstanding of the problem (known, asked), error in  solving the problem, error writing the final answer, b) the type of  students error on XI grade MA in solving matrix problem are: concept errors, principle errors, operating errors, the other errors (write the final answer), c) factor of students  error on XI grade MA in solving matrix problem are: less understanding of mathematical concepts, less have sufficient on  cognitive abilities about matrix principles, less understanding of command questions, not careful and skillful in calculations, less have sufficient on  cognitive abilities to solving matrix problems, forgot, less accuracy, and less have skill abaout operation symbols.